AKTIVITAS ANTIBAKTERI EKSTRAK DAN FRAKSI N-HEKSANA KULIT BUAH KAKAO (Theobroma cacao L.) - Purnama, Agnia; Ginting, Binawati; Yahya, Mustanir; Afifi, Muhammad Ridho; Maghfirah, Ruhul; Farida, Mutia; Hamdiyati, Hamdiyati (UIN AR-RANIRY, 2025)
This study aims to evaluate the antibacterial activity of the n-hexane extract and fraction of cocoa pod husk against Staphylococcus aureus. The antibacterial was tested using the paper disc diffusion method. The results showed that the extract inhibited bacterial with inhibition zones of 7.13 ± 0.29; 8.58 ± 0.14; 9.60 ± 0.87; and 10.97 ± 0.08 mm at concentrations of 1%, 5%, 10%, and 20%, respectively. The fractionation process produced 9 fractions and the 9th fraction showed the greatest inhibitory activity with inhibition zone diameters of 7.42 ± 0.03; 9.22 ± 0.03; 10.43 ± 0.03; and 11.83 ± 0.03 mm at concentrations of 1%; 5%; 10%; and 20% respectively. Phytochemical analysis and thin-layer chromatography (TLC) showed the presence of terpenoid and steroid compounds. Based on the antibacterial activity exhibited by the extract and fraction, this plant shows potential to be developed as a source of natural antibacterials.